A strategic management paper for Pacific Arts and Decor International, Inc. - Magpantay, Edna Elena DC. (Animo Repository, 1999)
The company under study, Pasific Arts and Decor International, Inc. or PADI, Inc. is engaged in the export of furniture. It has been in the business for quite some time and remains to be competitive in spite of numerous setbacks in relation to the economic situation our country has faced in the past. An in depth study of the industry has been undertaken to understand the environment where the company is performing and at the same time explore other possibilities and potential that the comapny may venture into to maintain or even edge over its other competitors. An evaluation of company's performance was also undertaken to see whether it is at par with other players in the industry. The different strategies of the company was analyzed based on two frameworks, namly the value chain and the frameworks made by C.K. Pralahad and Gary Hamel in their book entitled Competing for the Future . It is necessary to take two different frameworks since tha value chain evaluates the company's performance putting emphasis on its operations while the frameworks of the two authors evaluates the over-all strategy of the company in the future. In addition, the company is evluated also based on market trends and future developments to determine whether the company still has greater potential for groeth helping them get better threshold on competition and prepare itself to go global. All current and recommended strategies are presented side by side to show a comparative analysis and for easy understanding of which of these are to be adopted . This isbacked by financial projections to support the recommendations. All these are being done with the end in view of gaining for the company a competitive advantage over others and prepare itself to be an active performer in the global market which is starting to be the trend of many business today.